Anthropometric and biomechanical characteristics of body segments in persons with spinal cord injury. (11th April 2017) - Fang, Y.; Morse, L.R.; Nguyen, N.; Tsantes, N.G.; Troy, K.L.
Abstract: People with spinal cord injury (SCI) experience bone and muscle loss in their paralyzed limbs that is most rapid and severe in the first 3 years after injury. Restoration of mechanical loading through therapeutic physical activity may potentially slow or reverse post-SCI bone loss, however, therapeutic targets cannot be developed without accurate biomechanical models. Obesity is prevalent among SCI population, and it alters body composition and further affects parameters of these models. Here, clinical whole body dual-energy X-ray absorptiometry data from people with acute ( n = 39) and chronic ( n = 61) SCI were analyzed to obtain anthropometric parameters including segment masses, center of mass location, and radius of gyration for both obese and non-obese individuals. Chronic SCI was associated with higher normalized trunk mass of 3.2%BW and smaller normalized leg mass of 1.8%BW in males, but no significant changes in segment centers of mass or radius of gyration. People with chronic SCI had 58.6% lean mass in the trunk, compared to 66.6% lean mass in those with acute SCI ( p = 0.01), with significant changes in all segments. Obesity was associated with an increase in trunk mass proportion of 3.1%BW, proximal shifts in thigh and upper arm center of mass, and changes to thigh and shank radius of gyration. The data presented here can be used to accurately represent the anthropometrics of SCI population in biomechanical studies, considering obesity and injury duration.